New horizons of international law and developing countries - "Agrawala,S.K (ed) ;Rao,T.S.Rama(ed) ; Saxena,J.N(ed)" (Bombay, 1983)
This publication contains the contribution of well -known Indian Public International teachers. They cover areas of transnational activities which International law has been endeavoring to regulate. The problems and perspectives of teaching and research in International law in India, discussed in this volume, are perhaps common with those of other developing countries.
Keywords: International law